2006
DOI: 10.1038/sj.tpj.6500391
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic fluoxetine upregulates activity, protein and mRNA levels of cytosolic phospholipase A2 in rat frontal cortex

Abstract: Chronic lithium and carbamazepine, which are effective against mania in bipolar disorder, decrease the activity of cytosolic phospholipase A 2 (cPLA 2 ) and the turnover rate of arachidonic acid in phospholipids in rat brain. Assuming that stages of bipolar disorder are related to brain arachidonic acid metabolism, we hypothesized that drugs effective in depression would increase cPLA 2 activity. To test this hypothesis, adult male CDF-344 rats were administered fluoxetine (10 mg/kg intraperitoneally (i.p.) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 70 publications
5
22
1
Order By: Relevance
“…These findings are consistent with the short half-life of cPLA 2 mRNA (3-4 h) (Tay et al 1994) and the rapid washout of fluoxetine and norfluoxetine from rat brain (Caccia et al 1990). Chronic (but not acute) fluoxetine has been shown to increase cPLA 2 protein and mRNA in the rat frontal cortex, likely by increasing the level of AU-rich element/poly(U)-binding/degradation factor which stabilizes cPLA 2 mRNA (Rao et al 2006). The increased protein level of cPLA 2 observed in the current study is likely explained by chronic fluoxetine's ability to increase cPLA 2 mRNA.…”
Section: Kineticssupporting
confidence: 45%
“…These findings are consistent with the short half-life of cPLA 2 mRNA (3-4 h) (Tay et al 1994) and the rapid washout of fluoxetine and norfluoxetine from rat brain (Caccia et al 1990). Chronic (but not acute) fluoxetine has been shown to increase cPLA 2 protein and mRNA in the rat frontal cortex, likely by increasing the level of AU-rich element/poly(U)-binding/degradation factor which stabilizes cPLA 2 mRNA (Rao et al 2006). The increased protein level of cPLA 2 observed in the current study is likely explained by chronic fluoxetine's ability to increase cPLA 2 mRNA.…”
Section: Kineticssupporting
confidence: 45%
“…The present observations confirm the observations by Qu et al (2006), Rao et al (2006), and Lee et al (2008) who showed fluoxetine-mediated upregulation of cPLA 2 activity and expression in intact brain by demonstrating similar cPLA 2 upregulation by fluoxetine in astrocytes, a brain cell type that constitutes about 20% in gray matter (Hertz 2008) and may be the site of most of its cPLA 2 expression (Lautens et al 1998;Balboa and Balsinde 2002;Sun et al 2004). They provide no information whether neurons may respond in a similar manner, but attempts to treat neurons chronically with fluoxetine failed, because the neuronal cultures did not tolerate the treatment well (Li and Peng, unpublished experiments).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the results by Rao et al (2006), cPLA 2a was found to be upregulated, whereas the two other forms of PLA 2 , sPLA 2 and iPLA 2 , were unaffected. Since these cultures express no serotonin transporter (Kong et al 2002;Li and Peng, unpublished experiments) and any 5-HT present in the serum added to the culturing medium is rapidly metabolized by the high monooxidase activity in the cells Hertz 1982, 1983), the upregulation cannot be caused by inhibition of 5-HT uptake, but must be a direct effect of fluoxetine, i.e., of stimulation of 5-HT 2B receptors.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations